KRITIK DAN PENOLAKAN ULAMA HANBALI ATAS PEMIKIRAN TEOLOGI IBNU TAIMIYYAH - Badrus Samsul Fata (Institut Binamadani Indonesia, 2023)
Ibnu Taimiyyah (d. 728 H) has been the source of tension between his supporters and opponents for centuries. These supporters believed that Ibn Taimiyyah was ma'shum, more superior to Imam Ahmad bin Hanbal, and they even believed he was the ultimate mujtahid (khatim al-mujtahidin). However, such claims ignore the sharp rejection of Sunnis schools and generations (Hanafiyyah, Malikiyyah, Syafi'iyyah) and even the internal assessments of the Hanbali scholars such as Imam Ibn Rajab al-Hanbali (w. 795H), Imam Ibnu al-Mardawi al-Hanbali (w. 885H), Imam Ibnu Najjar al-Hanbali (w. 972H), Imam al-Buhuti al-Hanbali (w. 1051H), dan Imam al-Safarayni al-Hanbali (w. 1188H). This paper uses an interdisciplinary approach to analyze primary sources to demonstrate the referential hierarchy as the internal consensus of the Hanbali school (ijma' fi al-madhabihi), as the dispute over the results of tarjih formulation in ushul and furu' comes up. The first rank is the founding father of Hanbali school, Imam Ahmad bin Hanbal himself. The second place is Imam Ibnu Qudamah al-Maqdisi al-Hanbali, the writer of Kitab al-Kafi fi Fiqh al-Imam Ahmad bin Hanbal and Kitab al-Mughni. The third contributor is Imam Majduddin Abu al-Barakah al-Taimy, the writer of Kitab al-Muharrar fi al-Fiqh. The fourth rank belongs to Imam Ibn Muflih al-Hanbali, Kitab al-Furu's writer. The fifth place is Imam Ibnu Rajab al-Hanbali, the writer of Kitab al-Qawa'id al-Fiqhiyah. The sixth rank is Imam Ibnu Hamdan al-Hanbali, the writer of Kitab al-Ri'ayah al-Kubra. The seventh contributor is Imam Taqiyyuddin Ibn Taimiyyah, who wrote Kitab Majmu' al-Fatawa. The eighth rank is Imam Ibn 'Abdus al-Hanbali, the writer of Kitab al-Tadhkirah fi al-Fiqh. Furthermore, this article also proves that Ibn Taymiyyah is not the only scholar of the Hanbali school to hold the title of Syaikhul Islam among Hanbali scholars; there are still many others. Instead, Syaikhul Imam Abdul Qadir al-Jilani al-Hanbali received a more prestigious title as the Sultan-al-Masyayikh among the leading scholars of the Hanbali school.